Patient care standards for primary mitochondrial disease in Australia: an Australian adaptation of the Mitochondrial Medicine Society recommendations. Issue 1 (19th November 2021) - Sue, Carolyn M.; Balasubramaniam, Shanti; Bratkovic, Drago; Bonifant, Catherine; Christodoulou, John; Coman, David; Crawley, Karen; Edema‐Hildebrand, Fabienne; Ellaway, Carolyn; Ghaoui, Roula; Kava, Maina; Kearns, Lisa S.; et al.
Abstract: This document provides consensus‐based recommendations for general physicians and primary care physicians who diagnose and manage patients with mitochondrial diseases (MD). It builds on previous international guidelines, with particular emphasis on clinical management in the Australian setting. This statement was prepared by a working group of medical practitioners, nurses and allied health professionals with clinical expertise and experience in managing Australian patients with MD. As new treatments and management plans emerge, these consensus‐based recommendations will continue to evolve, but current standards of care are summarised in this document.